Emissive‐Dye/Cucurbit[n]uril‐Based Fluorescence Probes for Sensing Applications. Issue 10 (7th March 2023) - Chatterjee, Sobhan; Liang, Feng
Abstract: Supramolecular host‐guest chemistry has provided many opportunities for the design and construction of new fluorescent systems in various applications, particularly in the field of sensing. Owing to the special structure and fascinating utilities, cucurbit[n]urils (CB[n]s) existing themselves as a young family of molecular vessels, it construction a stable host‐guest supramolecular complex with a variety of fluorescent dyes and indicators, that has been used as a powerful fluorescent probe and is widely used in sensing and related research fields. Therefore, in this review article, we will outline and attention on the recent advances in the progress of various CB[n] ⋅ guest‐based fluorescent probes, it can provide a general overview of the construction, detection mechanism and fluorescence sensing of certain metal ions, biomolecules and toxic chemicals. Examples of the selection of other types of CB[n]‐based supramolecular assemblies and coordination polymers will also be covered. Finally, we will also provide important views on fluorescent CB[n] ⋅ guest‐based inclusion complex for metal ion and biomolecular sensors. Abstract : CB[n]s‐based host‐guest complexes are promising nanosensor for applications in the environmental and biological fields. In this review, various fluorescent dye containing CB[n]s ⋅ Dye inclusion complexes are systematically summarized and discussed from their designing chemosensors to their applications in metal ions, biomolecules and some toxic chemical.